Long Term Medical Treatment and Vestibular Rehabilitation in A Patient with Complicated Active Bilateral Meniere's Disease - Sadegh Jafarzadeh; Mohammad Reza Golrokhian Sani (Shiraz University of Medical Sciences, 2019)
Background: Bilateral Meniere's disease presents with attacks of vertigo leading to severe imbalance and oscillopsia. Sometimes, treatment of bilateral Meniere's disease is challenging. The following case report presents an appropriate and successful management for a complicated Bilateral Meniere's disease. Presentation of Case: Patient was a 42 years male referred with severe attacks of vertigo, severe to profound bilateral hearing loss and severe tinnitus as well as imbalance. Vestibular assessment was done with electronystagmography, head impulse test, cervical and ocular vestibular evoked myogenic potential that showed bilateral and widespread vestibular abnormality in the semicircular canals and otolith systems. Patient had different medical treatments before referring to us and we started some medical and rehabilitation treatments based on his unstable conditions and followed him up for over three years. Discussion: Vestibular rehabilitation is an approach for the management of many vestibular abnormalities such as Meniere's disease. It could help to resolve vertigo and imbalance in acute and chronic stage of Meniere's disease. Conclusion: Vestibular rehabilitation may be helpful in controlling the acute symptoms and helps to improve imbalance and oscillopsia.